OP0022 Targeting Fibroblastoid-like Cells by Drug Loaded Engineered Gold Nanoparticles as A Novel Approach for ILD-SSC Treatment. (15th July 2016) - Cova, E.; Codullo, V.; Inghilleri, S.; Colombo, M.; Prosperi, D.; Meloni, F.; Montecucco, C.
Abstract : Background: Systemic Sclerosis (SSc) is an autoimmune fibrotic disorder characterised by collagen and extracellular matrix deposition in the skin and internal organs, such as the lung. Interstitial lung involvement (ILD) is frequent in SSc but effective therapies are lacking and ILD represents one of the most frequent causes of death. Gold nanoparticles (GNPs) have a great potential in biomedical applications among which drug-delivery. Previously, we proved that GNPs containing everolimus and functionalized with anti-CD44 antibody targeted to mesenchymal cells from patients with chronic lung allograft rejection (CLAD) specifically inhibited these cells. We proved that also fibroblastoid-like cells (FLCs) isolated from bronchoalveolar lavage (BAL) of ILD-SSc patients express CD44. Objectives: we loaded GNPs with the drug imatinib (GNP-HCim) with the aim to specifically inhibit FLCs from ILD-SSc patients. Methods: GNPs with imatinib and exposing an anti-CD44 antibody were engineered, as previously described (1). GNP-HCim were incubated 2h with FLCs from three patients with ILD-SSc. Cell apoptosis (Annexin V) and proliferation (CFSE) were evaluated at different times by flow cytometry. Cell viability was assessed by MTT test. As control, functionalized GNPs without imatinib (GNP-HC) or imatinib alone (IM) were used. Fluorescent GNP-HC were generated to assess cell uptake by confocal microscopy and flow cytometry. Statistical differences were evaluated using ANOVA by Graph Prism 5.0 program. Results: Fluoresce experiments showed that only HC-functionalized nanoparticles entered FLCs within 1 h. The results showed that GNP-HCim inhibited cell proliferation without significant differences between the three cell lines. In particular, the effect of GNP-HCim was significant at 48 (p<0.001) and 72h (p<0.01). A significant inhibition was also observed in presence of GNP-HC both after 48 (p<0.01) and 72h (p<0.05). No changes were produced by IM alone (fig. 1). MTT assay confirmed the results obtained by CFSE since a significant reduction (p<0.001) of cell viability was observed with GNP-HCim and GNP-HC starting from 48 h. IM treatment affected the FLCs viability (p<0.05 at 48h; p<0.001 at 72h). Functionalized nanoparticles were able to significantly increase apoptosis after 8 (p=0.0051) and 24 h (p<0.001) compared to uFLCs. However, only drug-loaded nanoparticles still significantly increased apoptotic rate after 48 h (p=0.004). Conclusions: We proved that specifically engineered GNPs significantly inhibit proliferation and induce apoptosis of FLCs from ILD-SSc patients, as already described for CLAD patients. FLCs treatment with imatinib alone was not effective as GNP-HCim demonstrating the superiority of the nanoparticles. Our results also suggest an unspecific effect of nanoparticles themselves which has to be further clarified before the possibility to use engineered nanoparticles to develop new pharmacological treatment for patients with pulmonary fibroproliferative disorders. References: Cova E, Colombo M, Inghilleri S, et al. Nanomedicine 2015. Disclosure of Interest: None declared